Cross-Country Comparative Analysis of Legislation and Court Rulings in Wrongful Birth Actions. Issue 1 (2nd January 2019) - Scurria, Serena; Asmundo, Alessio; Gualniera, Patrizia
Abstract: Negligent conduct by health care providers can result in medical malpractice injury sustained by parents denied their right to decide whether and when to have children. In this review of the international medicolegal literature, the authors present a comparative analysis of the law of medical negligence in this context and a discussion of the grounds for compensable injury resulting from medical error. The discussion is focused on the legal provisions for compensable injury awarded to the plaintiff (expectant mother, parents of the born child, and born child) and the types of injury various legal systems recognize in such cases. The aim of this article is to provide medical malpractice investigators and legal professionals with an overview of the birth cases.